Melasma: tratamento e suas implicações estéticas - Kledson Lopes BARBOSA; Monique Ribeiro Mota GUEDES (Federal Council of Pharmacy, 2018)
Melasma is part of a biological phenomenon, developed from exposure to UV rays, use of exogenous hormones, genetic factors, and drugs that cause photosensitization. It is known that the incidence occurs mainly in women of childbearing age. Hyperpigmentation is a skin disease that arises after a cutaneous lesion due to an inflammatory reaction. Melasma and hyperpigmentation are two relatively frequent conditions, and because of the frequency with which they resurface after treatment, it is extremely important to know them to obtain essential information of an effective therapy without resurgence. In this sense, the objective of this study was to perform a literature review on melasma and hyperpigmentation contemplating the pathophysiology and main treatments used. For this, a study was developed as exploratory-descriptive qualitative research carried out in international journals from November 2016 to April 2017. It is concluded that the treatment protocols have progressed in recent years. However, the actual pathogenesis of melasma remains somewhat unsatisfactory and that topical agents and systems that use laser sometimes induce improvement of pigmentation and not total elimination of the lesion.